OPTIMIZATION OF FAST-MOVING DRUG INVENTORY USING THE WEIGHTED PRODUCT METHOD AT ANNISA DRUGSTORE - Rafika Dayanti; Neni Mulyani; Ahmad Muhazir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2026)
Abstract: Managing fast-moving drug inventory requires accurate supplier selection to ensure product availability and minimize the risk of overstock and out-of-stock conditions. At Annisa Pharmacy, the supplier selection process has traditionally relied on experience and subjective judgment, which may lead to less optimal decisions. This study aims to design and implement a Decision Support System (DSS) for selecting fast-moving drug suppliers using the Weighted Product (WP) method. The WP method is applied because it is capable of processing multiple criteria simultaneously through structured weighting, including demand frequency, delivery lead time, remaining shelf life, purchase price, and profit margin. The system is developed as a web-based application using PHP and MySQL. The results show that the implementation of the Weighted Product method successfully produces preference values and accurate supplier rankings, enabling the system to correctly determine the most optimal fast-moving drug supplier based on the defined criteria. Therefore, the developed system can assist the owner of Annisa Pharmacy in making more precise, objective, and structured inventory procurement decisions. Keywords: decision support system; drug inventory; supplier selection; weighted product. Abstrak: Pengelolaan stok obat fast moving di Toko Obat Annisa memerlukan ketepatan dalam menentukan supplier agar ketersediaan obat tetap terjaga dan risiko overstock maupun out of stock dapat diminimalkan. Selama ini, proses pemilihan supplier masih dilakukan secara konvensional berdasarkan pengalaman, sehingga berpotensi menghasilkan keputusan yang kurang optimal. Penelitian ini bertujuan untuk merancang dan mengimplementasikan Sistem Pendukung Keputusan (SPK) pemilihan supplier obat fast moving menggunakan metode Weighted Product (WP). Metode WP digunakan karena mampu mengolah beberapa kriteria secara simultan melalui pembobotan yang terstruktur, meliputi frekuensi permintaan, lead time, sisa masa kedaluwarsa, harga beli, dan margin keuntungan. Sistem dikembangkan berbasis web menggunakan bahasa pemrograman PHP dan basis data MySQL. Hasil penelitian menunjukkan bahwa penerapan metode Weighted Product mampu menghasilkan nilai preferensi dan perankingan supplier secara objektif, sehingga sistem berhasil menentukan supplier obat fast moving yang paling optimal sesuai dengan kriteria yang telah ditetapkan. Dengan demikian, sistem yang dibangun dapat membantu pemilik Toko Obat Annisa dalam mengambil keputusan pengadaan stok obat secara lebih tepat, objektif, dan terstruktur. Kata kunci: sistem pendukung keputusan; toko obat; pemilihan pemasok; weighted product